AR film, light-transmitting assembly and electronic equipment

By adopting multi-layer film structure and magnetron sputtering coating technology, the existing anti-reflection films for vehicles have been solved, and the hardness of the film surface is improved, and the wear resistance and corrosion resistance are enhanced. , and the improvement of optical performance.

CN119471869APending Publication Date: 2025-02-18ZHEJIANG RIJIU NEW MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411656340.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing anti-reflective films for on-board vehicles are reddish in color, which affects the appearance of the vehicle and lacks solutions to improve the hardness, wear resistance and corrosion resistance of the film surface.

Method used

Using a multi-layer film structure, including a base layer, a base coating, a hardened layer, a niobium oxide layer, a silicon dioxide layer, a hybrid target layer and a metal-plated nickel-chromium layer, the film's light transmission is improved through magnetron sputtering coating technology. and durability.

Benefits of technology

The film surface hardness is improved, wear resistance and corrosion resistance are enhanced, and the reflectivity is reduced, especially in the range of 380-780nm, the average reflection is less than 1.0%, and the average reflection is less than 0.5% in the range of 400-700nm. , and the total light transmittance reaches more than 93%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119471869A_ABST
    Figure CN119471869A_ABST
Patent Text Reader

Abstract

The invention discloses an AR film, a light-transmitting assembly and electronic equipment, the AR film comprises a base material layer, and a lower bottom coating and a lower HC hardening layer are sequentially arranged on one side of the base material layer in the direction away from the base material layer; an upper priming coat, an upper HC hardening layer, a priming coat, a first niobium oxide plating layer, a first silicon dioxide plating layer, a first mixed target plating layer, a second niobium oxide plating layer, a second mixed target plating layer, a metal nickel-chromium plating layer and a second silicon dioxide plating layer are sequentially arranged on the other side of the base material layer in the direction away from the base material layer; wherein the thickness of the plated metal nickel-chromium layer is 0.1-10nm, the nickel accounts for 40-95wt% of the layer, and the balance is chromium; wherein the base layer, the first niobium oxide plated layer, the first silicon dioxide plated layer, the first mixed target plated layer, the second niobium oxide plated layer, the second mixed target plated layer and the second silicon dioxide plated layer are plated by magnetron sputtering. According to the invention, by optimizing the structural composition of the film, the deposition of the functional layer is directly realized through magnetron sputtering, and the control of the visual effect of the product is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electronic technology, and in particular relates to an AR film, a light-transmitting component and an electronic device. Background Art

[0002] The anti-reflective film for vehicles is closely related to the production and sales volume of automobiles. As a major automobile consumer country, my country's automobile production and sales account for more than 30% of the world's total, which is a huge amount. Therefore, the demand for anti-reflective film for vehicles is also huge. The existing film is reddish in color, which seriously affects the appearance of vehicles.

[0003] Therefore, in view of the above technical problems, it is necessary to provide an AR film, a light-transmitting component and an electronic device.

[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0005] The object of the present invention is to provide an AR film, a light-transmitting component and an electronic device.

[0006] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:

[0007] The AR film comprises a substrate layer,

[0008] In a direction away from the substrate layer, a lower primer layer and a lower HC hardening layer are sequentially arranged on one side of the substrate layer;

[0009] In the direction away from the substrate layer, an upper primer layer, an upper HC hardening layer, a primer layer, a first niobium oxide-plated layer, a first silicon dioxide-plated layer, a first mixed target layer, a second niobium oxide-plated layer, a second mixed target layer, a metal nickel-chromium-plated layer and a second silicon dioxide-plated layer are sequentially arranged on the other side of the substrate layer; wherein the metal nickel-chromium-plated layer has a thickness of 0.1-10 nm, and the nickel content of the layer is 40-95 wt%, and the balance is chromium;

[0010] The base layer, the first niobium oxide coating layer, the first silicon dioxide coating layer, the first mixed target coating layer, the second niobium oxide coating layer, the second mixed target coating layer and the second silicon dioxide coating layer are formed by magnetron sputtering.

[0011] In one or more embodiments of the present invention, the gas bombarding the target material during magnetron sputtering is argon gas.

[0012] In one or more embodiments of the present invention, the mass ratio of silicon to aluminum elements in the target material for coating the mixed target layer is: Si:Al=(80-95):(20-5).

[0013] In one or more embodiments of the present invention, the target material of the base layer is selected from: SiO2, Ti, Si, Al, MgF2, SiO, Sn, and Y.

[0014] In one or more embodiments of the present invention, the substrate layer is selected from a PET layer, a PI layer, a SRF layer, a TAC layer, a COP layer, and a PC layer.

[0015] In one or more embodiments of the present invention, during magnetron sputtering, the reaction gas of the target material is a mixed gas, and the mixed gas includes at least nitrogen and oxygen.

[0016] In one or more embodiments of the present invention, the mixed gas includes oxygen for controlling the voltage, and the content of oxygen therein is 5-10 v / v%.

[0017] In one or more embodiments of the present invention, a high temperature protection film is further included in the outermost layer away from the substrate layer.

[0018] In one or more embodiments of the present invention, a light-transmitting component includes a light-transmitting carrier and an AR film formed on the light-transmitting carrier.

[0019] In one or more embodiments of the present invention, an electronic device includes a main body and a light-transmitting component connected to the main body.

[0020] AR film, also known as (anti-reflection film), is a high-transmittance optical film that reduces reflection and allows light to pass more completely. AR film has the following functions: reduce or eliminate reflected light from optical surfaces such as prisms and plane mirrors, thereby increasing the light transmittance of these components and presenting the light to the user's eyes to the greatest extent. Due to the performance of the AR film itself, it is usually used in display device protection screens such as car displays, TVs, computers, mobile phones, tablets and other electronic products that increase transmittance and reduce reflectivity. The AR film can effectively increase the glass transmittance and reduce the glass reflectivity.

[0021] Compared with the prior art, the AR film, light-transmitting component and electronic device of the present invention can improve the film surface, increase hardness, increase wear resistance and enhance corrosion resistance, and increase durability during user use. In addition, an appropriate amount of adding a metal NiCr layer can reduce the a* value, reduce the red color, and make the color look more neutral or cool. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 1 is a comparison diagram of the reflection curves of the AR film in one embodiment of the present invention: wherein a is a curve reflecting 380-780nm, and b is a curve reflecting 400-700nm. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0025] The AR film in one embodiment of the present invention includes a substrate layer (the substrate of the two-proof film can be a PET layer, a transparent PI layer or an SRF layer, and the substrate of the three-proof film can be a TAC, a COP layer or a PC layer), the substrate layer thickness is 5.7-250μm, and the application range is different. The substrate layer is provided with an upper primer layer and a lower primer layer on both sides through a coating process, and an upper HC hardening layer and a lower HC hardening layer are provided on the upper primer layer and the lower primer layer through a coating process, and both are obtained by coating with an acrylic resin coating liquid, the upper HC hardening layer has a coating thickness of 0.3-3.1μm, and the lower HC hardening layer has a coating thickness of 0.2-4.1μm. After coating, a 30-188μm high-temperature protective film is attached to the lower HC hardening layer to ensure the appearance protection of the film surface and the stability of the coating during the magnetron sputtering coating process. A primer layer is then plated on the upper HC hardening layer by magnetron sputtering process to increase the adhesion of the bottom layer. The raw materials of the primer layer can be SiO2, Ti, Si, Al, MgF2, SiO, Sn, Y, etc. The coating of the primer layer greatly improves the adhesion performance of the film surface. A first niobium oxide (NB2O5) layer (5-200nm) is plated on the primer layer to increase the transmittance, a first silicon dioxide (SIO2) layer (10-260nm) is plated on the first niobium oxide layer to reduce the reflection, and a first mixed target layer (20-110nm) is formed on the first silicon dioxide layer. The target material ratio (Si:Al is between 85-98:15-2) is plated on the first mixed target layer. ), a second mixed target layer (50-310nm) for reducing reflection is plated on the second niobium oxide layer, the target material ratio (Si:Al is between 85-98:15-2), a metal nickel-chromium (NiCr) layer (0.1-10nm) for increasing hardness, wear resistance and corrosion resistance is plated on the second mixed target layer, the target material ratio (nickel accounts for 40-95%, chromium accounts for 5-60%), and then a second silicon dioxide layer (50-20nm) is plated on the metal nickel-chromium layer.

[0026] In the above implementation scheme, since the top layer is a sputtered second silicon dioxide layer, oxygen is needed to control the voltage, and there is a problem of stability difference, which will cause slight fluctuations in uniformity, making the product more obviously unstable and affecting the overall coating uniformity. In response to this problem, the present application additionally sets up a silicon-aluminum mixed target. A small amount of doped alloy aluminum will make the target material sputtering more stable, the output stable, and the voltage fluctuation small, making the sputtering more uniform and the efficiency more consistent. In addition, during the entire magnetron coating sputtering process, the gas used to bombard the target material is argon, and the target material reaction gas is a nitrogen-oxygen mixed gas, which further solves the uniformity of the silicon target film surface and improves the overall optical stability after superposition. In general, the uniformity of the reflected light at 380-780nm of the film product is within 5%, and the color difference in the TD direction is basically small, which is of great help to the yield rate and product stability. The total light transmittance can reach more than 93%, and the spectral transmittance of 400-700nm can reach more than 93%. The average reflection of 380-780nm is less than 1.0%, and the average reflection of 400-700nm is less than 0.5%.

[0027] Furthermore, after the magnetron coating is completed, a layer of AF layer (2-190 nm) with anti-oil, anti-fingerprint and anti-scratch properties can be coated on the surface, which is mainly obtained by coating with a perfluoropolyether coating.

[0028] Including but not limited to the following embodiments, the conditions of magnetron sputtering are: acceleration voltage: 300 V, magnetic field: about 80 G, gas pressure: 1 mTorr, current density: 4 mA / cm2, power density: 10 W / cm2.

[0029] Example 1

[0030] The AR film of this embodiment includes a PET substrate layer with a thickness of 5.7μm. The substrate layer is coated with an upper primer layer and a lower primer layer made of polyester emulsion on both sides through a coating process. The upper primer layer and the lower primer layer are coated with an upper HC hardening layer and a lower HC hardening layer respectively through a coating process. Both are obtained by coating with an acrylic resin coating liquid. The coating thickness of the upper HC hardening layer is 0.3μm, and the coating thickness of the lower HC hardening layer is 0.2μm. After coating, a 30-188μm high-temperature protective film is attached to the lower HC hardening layer to ensure the appearance protection of the film surface and the stability of the coating during the magnetron sputtering coating process. A primer layer is then plated on the upper HC hardening layer through a magnetron sputtering process to increase the adhesion of the bottom layer. The raw material of the primer layer can be Ti. A first niobium oxide (NB2O5) layer (5nm) for increasing transmittance is plated on the base layer, a first silicon dioxide (SIO2) layer (10nm) for reducing reflection is plated on the first niobium oxide layer, a first mixed target layer (20nm) is formed on the first silicon dioxide layer, the target material ratio (Si:Al is 85:15), a second niobium oxide layer (5nm) for increasing transmittance is plated on the first mixed target layer, a second mixed target layer (50nm) for reducing reflection is plated on the second niobium oxide layer, the target material ratio (Si:Al is 85:15), a metal nickel-chromium (NiCr) layer (0.1nm) for increasing hardness, wear resistance and corrosion resistance is plated on the second mixed target layer, the target material ratio (nickel accounts for 40% and chromium accounts for 60%), and then a second silicon dioxide layer (50nm) is plated on the metal nickel-chromium layer.

[0031] Comparative Example 1

[0032] The AR film of this comparative example includes a PET substrate layer with a thickness of 5.7 μm. The substrate layer is coated with an upper primer layer and a lower primer layer made of polyester emulsion on both sides through a coating process. The upper primer layer and the lower primer layer are coated with an upper HC hardening layer and a lower HC hardening layer respectively through a coating process. Both are obtained by coating with an acrylic resin coating liquid. The coating thickness of the upper HC hardening layer is 0.3 μm, and the coating thickness of the lower HC hardening layer is 0.2 μm. After coating, a 30-188 μm high-temperature protective film is attached to the lower HC hardening layer to ensure the appearance protection of the film surface and the stability of the coating during the magnetron sputtering coating process. A primer layer is then plated on the upper HC hardening layer through a magnetron sputtering process to increase the adhesion of the bottom layer. The raw material of the primer layer can be Ti. A first niobium oxide (NB2O5) layer (5nm) for increasing transmittance is plated on the base layer, a first silicon dioxide (SIO2) layer (10nm) for reducing reflection is plated on the first niobium oxide layer, a first mixed target layer (20nm) is formed on the first silicon dioxide layer, the target material ratio (Si:Al is 85:15), a second niobium oxide layer (5nm) for increasing transmittance is plated on the first mixed target layer, a second mixed target layer (50nm) for reducing reflection is plated on the second niobium oxide layer, the target material ratio (Si:Al is 85:15), and a second silicon dioxide layer (50nm) is plated on the second mixed target layer.

[0033]

[0034] Table 1 Comparison of pencil hardness between comparative example 1 and embodiment 1

[0035] As can be seen from Table 1, the unified test method, the film material is placed on the glass panel, the pencil hardness tester is loaded with 500g, the hardness of the coating surface is tested, according to the test index requirements, ≥3H (500g), the test instrument model is ASTM D3363, the 3H hardness pencil result is slightly worse than that of Example 1, and the 4H pencil hardness result is significantly worse than that of Example 1. The pencil hardness tester is loaded with 750g, and the hardness of the coating surface is tested. The 3H hardness pencil result is significantly worse than that of Example 1, and the 4H pencil hardness result is significantly worse than that of Example 1. The 750g load is based on more stringent testing, which is not required in the product specification. Comparative Example 1 meets the test requirements. It can be seen from the comparison results in the above table that the pencil hardness of Example 1 is significantly better than that of Comparative Example 1.

[0036]

[0037] Table 2 Comparison of steel wool wear resistance between comparative example 1 and embodiment 1

[0038] As can be seen from Table 2, a unified test method is used, the film material is placed on a glass panel, the wear-resistant machine is loaded with 1000g, and the wear resistance of the coated surface is tested. There is no difference in the results of 2000 / 3000 tests. The comparative example has 5-10 scratches after 15000 tests. The wear resistance of Example 1 can reach 5000 times without any scratches on the surface, which shows that Example 1 is better.

[0039]

[0040]

[0041] Table 3 Comparison of various environmental tests between comparative example 1 and embodiment 1

[0042] As can be seen from Table 3, the unified test method is to adhere the OCA glue on the back before the ring test and stick it on the transparent glass. After bonding, use a degassing machine to degas. After degassing, wipe the surface clean. Test 100℃ water temperature for 3 / 5h, 100 grids, compared with 3h 100 grids, 5h comparative example 12-3B, and embodiment 1 are all 5B, indicating that embodiment 1 is better; test double 85 ring test (high temperature 85℃, high humidity 85%), compared with 32 days 100 grids, 36 days comparative example 11-3B, Example 1 is 5B, which shows that Example 1 is better; Test high temperature ring test (95°C), compared with 32 days 100 grids 5B, 36 days comparative example 12-3B, Example 1 is 5B, which shows that Example 1 is better; Test low temperature ring test (-40°C), compared with 32 days 100 grids 5B, 36 days comparative example 12-3B, Example 1 is 5B, which shows that Example 1 is better; Test sunlight resistance ring test (light 0.55w / (m 2 .nm), wavelength 340nm, filter Extended UV-Q / B, 3.8h of light + 1h of darkness as one cycle. The temperature of the illuminated blackboard was set at 89°C, the temperature of the box was 63°C, and the humidity was 50%; the temperature of the box and blackboard was set at 38°C and the humidity was 95% in the dark stage). Compared with 32 days, the average of 100 grids was 5B, and the average of 36 days of comparative example 12-3B, the average of Example 1 was 5B, indicating that Example 1 is better.

[0043]

[0044] Table 4 Transmission data comparison

[0045] According to the optical test requirements, the total light transmittance of the bare film test can reach more than 95%, and the spectral transmittance of 400-700nm can reach more than 93%. It can be seen from Table 4 above that there is basically no significant difference in transmittance between Comparative Example 1 and Example 1, indicating that the optical effect is OK.

[0046] According to the optical test requirements, the reflection 380-780nm average is less than 1.0%, and the 400-700nm average is less than 0.5%. The test method is to stick OCA glue on the back and stick it on the black acrylic board. After sticking, use a degassing machine to degas. After degassing, wipe the surface clean. Figure 1 As shown, there is basically no difference between the reflection curves of Comparative Example 1 and Example 1, with the average reflection values ​​of 380-780nm being 0.77 / 0.74% and the average reflection values ​​of 400-700nm being 0.26 / 0.28%, indicating that the optical effect is OK.

[0047]

[0048] Table 5 Color comparison

[0049] Test method: adhere OCA glue on the back and stick it on a black acrylic board. After bonding, use a degassing machine to degas. After degassing, wipe the surface clean. The L* value here represents brightness. It can be seen from Table 5 that there is basically no significant difference between Comparative Example 1 and Example 1; the a* value represents red and green, a* value of '+' indicates that the red color is heavy, and a* value of '-' indicates that the green color is heavy. It can be seen from Table 6 that the a* value of Comparative Example 1 is '+', and the a* value of Example 1 is '-'; the b* value represents yellow and blue, b* value of '+' indicates that the yellow color is heavy, and b* value of '-' indicates that the blue color is heavy. It can be seen from Table 5 that there is no significant difference in the b* value between Comparative Example 1 and Example 1. Comprehensive color comparison, the color of Comparative Example 1 is blue, but there will be a slight redness at different angles. Example 1 reduces the a* value, reduces the red color, and makes the color look more neutral or cool.

[0050] Example 2

[0051] The AR film of this embodiment includes a PI substrate layer with a thickness of 5.7μm, and the application scope is different. The upper and lower primer layers made of polyester emulsion are respectively provided on both sides of the substrate layer through a coating process. The upper and lower primer layers are respectively provided with an upper HC hardening layer and a lower HC hardening layer through a coating process. Both are obtained by coating with acrylic resin coating liquid. The coating thickness of the upper HC hardening layer is 3.1μm, and the coating thickness of the lower HC hardening layer is 4.1μm. After coating, a 188μm high-temperature protective film is attached to the lower HC hardening layer to ensure the appearance protection of the film surface and the stability of the coating during the magnetron sputtering coating process. A primer layer to increase the adhesion of the bottom layer is then plated on the upper HC hardening layer through a magnetron sputtering process. The raw material of the primer layer is Si, and the plating of the primer layer greatly improves the adhesion performance of the film surface. A first niobium oxide (NB2O5) layer (200nm) for increasing transmittance is plated on the base layer, a first silicon dioxide (SIO2) layer (260nm) for reducing reflection is plated on the first niobium oxide layer, a first mixed target layer (110nm) is formed on the first silicon dioxide layer, the target material ratio (Si:Al is 98:2), a second niobium oxide layer (280nm) for increasing transmittance is plated on the first mixed target layer, a second mixed target layer (310nm) for reducing reflection is plated on the second niobium oxide layer, the target material ratio (Si:Al is 98:2), a metal nickel-chromium (NiCr) layer (10nm) for increasing hardness, wear resistance and corrosion resistance is plated on the second mixed target layer, the target material ratio (nickel accounts for 95% and chromium accounts for 5%), and then a second silicon dioxide layer (20nm) is plated on the metal nickel-chromium layer. The unified test method is that the film material is placed on the glass panel, and the pencil hardness tester is loaded with 500g to test the hardness of the coating surface. According to the test index requirements, ≥3H (500g), the test instrument model is ASTM D3363, and the pencil hardness test in this embodiment meets the requirements.

[0052] The unified test method is that the film material is placed on the glass panel, the wear-resistant machine is loaded with 1000g, and the wear resistance of the coating surface is tested. The wear resistance of this embodiment can reach 5000 times without scratches on the surface.

[0053] Unified test method, before the ring test, the back side is attached with OCA glue and attached to the transparent glass. After the attachment, the degassing machine is used for degassing. After degassing, the surface is wiped clean, and the test is 100℃ water temperature boiling for 3 / 5h. The 100 grids of this embodiment for 3h are 5B, and the 5h of this embodiment are 5B; the double 85 ring test (high temperature 85℃, high humidity 85%) is tested for 32 days. The 100 grids of this embodiment are 5B, and the 5B of this embodiment are all 5B; the high temperature ring test (95℃) is tested, the 100 grids of this embodiment for 32 days are 5B, and the 5B of this embodiment for 36 days; the low temperature ring test (-40℃) is tested, the 100 grids of this embodiment for 32 days are 5B, and the 5B of this embodiment for 36 days; the sunlight resistance ring test (light 0.55w / (m 2.nm), wavelength 340nm, filter Extended UV-Q / B, 3.8h of light + 1h of darkness as one cycle. The temperature of the illuminated blackboard was set at 89°C, the temperature of the box was 63°C, and the humidity was 50%; the temperature of the box and blackboard was set at 38°C and the humidity was 95% in the dark stage. In this example, the average of 100 grids was 5B after 32 days, and the average of 100 grids was 5B after 36 days.

[0054] According to the optical test requirements, the total light transmittance of the bare film test can reach more than 95%, and the spectral transmittance of 400-700nm can reach more than 93%. There is basically no significant difference in the transmittance of the samples in this embodiment, indicating that the optical effect is OK.

[0055] According to the optical test requirements, the average reflection of 380-780nm is less than 1.0%, and the average reflection of 400-700nm is less than 0.5%. The test method is to stick OCA glue on the back and stick it on the black acrylic plate. After sticking, use a degassing machine to degass, and wipe the surface clean after degassing. In this embodiment, the average reflection of 380-780nm is 0.77 / 0.74%, and the average reflection of 400-700nm is 0.26 / 0.28%, which means that the optical effect is OK.

[0056] Test method: stick OCA glue on the back and stick it on a black acrylic board. Use a degassing machine to degas. Wipe the surface clean after degassing. The L* value here represents brightness. This embodiment reduces the a* value and reduces the red color, making the color look more neutral or cool.

[0057] Example 3

[0058] The AR film of this embodiment includes a COP substrate layer with a thickness of 5.7 μm and a different application range. The substrate layer is coated with an upper primer layer and a lower primer layer made of polyester emulsion on both sides through a coating process. The upper primer layer and the lower primer layer are coated with an upper HC hardening layer and a lower HC hardening layer respectively through a coating process. Both are obtained by coating with an acrylic resin coating liquid. The coating thickness of the upper HC hardening layer is 1.1 μm, and the coating thickness of the lower HC hardening layer is 2.1 μm. After coating, a 100 μm high-temperature protective film is attached to the lower HC hardening layer to ensure the appearance protection of the film surface and the stability of the coating during the magnetron sputtering coating process. A primer layer to increase the adhesion of the bottom layer is then plated on the upper HC hardening layer through a magnetron sputtering process. The raw material of the primer layer can be Si, and the coating of the primer layer greatly improves the adhesion performance of the film surface. A first niobium oxide (NB2O5) layer (100nm) for increasing transmittance is plated on the base layer, a first silicon dioxide (SIO2) layer (100nm) for reducing reflection is plated on the first niobium oxide layer, a first mixed target layer (60nm) is formed on the first silicon dioxide layer, the target material ratio (Si:Al is between 90:10), a second niobium oxide layer (100nm) for increasing transmittance is plated on the first mixed target layer, a second mixed target layer (100nm) for reducing reflection is plated on the second niobium oxide layer, the target material ratio (Si:Al is between 90:10), a metal nickel-chromium (NiCr) layer (0.1-10nm) for increasing hardness, wear resistance and corrosion resistance is plated on the second mixed target layer, the target material ratio (nickel accounts for 55% and chromium accounts for 45%), and then a second silicon dioxide layer (30nm) is plated on the metal nickel-chromium layer.

[0059] The unified test method is that the film material is placed on the glass panel, and the pencil hardness tester is loaded with 500g to test the hardness of the coating surface. According to the test index requirements, ≥3H (500g), the test instrument model is ASTM D3363, and the pencil hardness test in this embodiment meets the requirements.

[0060] The unified test method is that the film material is placed on the glass panel, the wear-resistant machine is loaded with 1000g, and the wear resistance of the coating surface is tested. The wear resistance of this embodiment can reach 5000 times without scratches on the surface.

[0061] Unified test method, before the ring test, the back side is attached with OCA glue and attached to the transparent glass. After the attachment, the degassing machine is used for degassing. After degassing, the surface is wiped clean, and the test is 100℃ water temperature boiling for 3 / 5h. The 100 grids of this embodiment for 3h are 5B, and the 5h of this embodiment are 5B; the double 85 ring test (high temperature 85℃, high humidity 85%) is tested for 32 days. The 100 grids of this embodiment are 5B, and the 5B of this embodiment are all 5B; the high temperature ring test (95℃) is tested, the 100 grids of this embodiment for 32 days are 5B, and the 5B of this embodiment for 36 days; the low temperature ring test (-40℃) is tested, the 100 grids of this embodiment for 32 days are 5B, and the 5B of this embodiment for 36 days; the sunlight resistance ring test (light 0.55w / (m 2 .nm), wavelength 340nm, filter Extended UV-Q / B, 3.8h of light + 1h of darkness as one cycle. The temperature of the illuminated blackboard was set at 89°C, the temperature of the box was 63°C, and the humidity was 50%; the temperature of the box and blackboard was set at 38°C and the humidity was 95% in the dark stage. In this example, the average of 100 grids was 5B after 32 days, and the average of 100 grids was 5B after 36 days.

[0062] According to the optical test requirements, the total light transmittance of the bare film test can reach more than 95%, and the spectral transmittance of 400-700nm can reach more than 93%. There is basically no significant difference in the transmittance of the samples in this embodiment, indicating that the optical effect is OK.

[0063] According to the optical test requirements, the average reflection of 380-780nm is less than 1.0%, and the average reflection of 400-700nm is less than 0.5%. The test method is to stick OCA glue on the back and stick it on the black acrylic plate. After sticking, use a degassing machine to degass, and wipe the surface clean after degassing. In this embodiment, the average reflection of 380-780nm is 0.77 / 0.74%, and the average reflection of 400-700nm is 0.26 / 0.28%, which means that the optical effect is OK.

[0064] Test method: stick OCA glue on the back and stick it on a black acrylic board. Use a degassing machine to degas. Wipe the surface clean after degassing. The L* value here represents brightness. This embodiment reduces the a* value and reduces the red color, making the color look more neutral or cool.

[0065] Example 4

[0066] The AR film of this embodiment includes a PC substrate layer with a thickness of 250μm, and the application scope is different. The upper and lower primer layers made of polyester emulsion are respectively provided on both sides of the substrate layer through a coating process. The upper and lower primer layers are respectively provided with an upper HC hardening layer and a lower HC hardening layer through a coating process. Both are obtained by coating with acrylic resin coating liquid. The coating thickness of the upper HC hardening layer is 0.3μm, and the coating thickness of the lower HC hardening layer is 0.2μm. After coating, a 30μm high-temperature protective film is attached to the lower HC hardening layer to ensure the appearance protection of the film surface and the stability of the coating during the magnetron sputtering coating process. A primer layer to increase the adhesion of the bottom layer is then plated on the upper HC hardening layer through a magnetron sputtering process. The raw material of the primer layer can be SiO2, and the coating of the primer layer greatly improves the adhesion performance of the film surface. A first niobium oxide (NB2O5) layer (50nm) for increasing transmittance is plated on the base layer, a first silicon dioxide (SIO2) layer (100nm) for reducing reflection is plated on the first niobium oxide layer, a first mixed target layer (20nm) is formed on the first silicon dioxide layer, the target material ratio (Si:Al is 85:15), a second niobium oxide layer (50nm) for increasing transmittance is plated on the first mixed target layer, a second mixed target layer (50nm) for reducing reflection is plated on the second niobium oxide layer, the target material ratio (Si:Al is 98:2), a metal nickel-chromium (NiCr) layer (60nm) for increasing hardness, wear resistance and corrosion resistance is plated on the second mixed target layer, the target material ratio (nickel accounts for 50% and chromium accounts for 50%), and then a second silicon dioxide layer (30nm) is plated on the metal nickel-chromium layer. The unified test method is that the film material is placed on the glass panel, and the pencil hardness tester is loaded with 500g to test the hardness of the coating surface. According to the test index requirements, ≥3H (500g), the test instrument model is ASTM D3363, and the pencil hardness test in this embodiment meets the requirements.

[0067] The unified test method is that the film material is placed on the glass panel, the wear-resistant machine is loaded with 1000g, and the wear resistance of the coating surface is tested. The wear resistance of this embodiment can reach 5000 times without scratches on the surface.

[0068] Unified test method, before the ring test, the back side is attached with OCA glue and attached to the transparent glass. After the attachment, the degassing machine is used for degassing. After degassing, the surface is wiped clean, and the test is 100℃ water temperature boiling for 3 / 5h. The 100 grids of this embodiment for 3h are 5B, and the 5h of this embodiment are 5B; the double 85 ring test (high temperature 85℃, high humidity 85%) is tested for 32 days. The 100 grids of this embodiment are 5B, and the 5B of this embodiment are all 5B; the high temperature ring test (95℃) is tested, the 100 grids of this embodiment for 32 days are 5B, and the 5B of this embodiment for 36 days; the low temperature ring test (-40℃) is tested, the 100 grids of this embodiment for 32 days are 5B, and the 5B of this embodiment for 36 days; the sunlight resistance ring test (light 0.55w / (m 2.nm), wavelength 340nm, filter Extended UV-Q / B, 3.8h of light + 1h of darkness as one cycle. The temperature of the illuminated blackboard was set at 89°C, the temperature of the box was 63°C, and the humidity was 50%; the temperature of the box and blackboard was set at 38°C and the humidity was 95% in the dark stage. In this example, the average of 100 grids was 5B after 32 days, and the average of 100 grids was 5B after 36 days.

[0069] According to the optical test requirements, the total light transmittance of the bare film test can reach more than 95%, and the spectral transmittance of 400-700nm can reach more than 93%. There is basically no significant difference in the transmittance of the samples in this embodiment, indicating that the optical effect is OK.

[0070] According to the optical test requirements, the average reflection of 380-780nm is less than 1.0%, and the average reflection of 400-700nm is less than 0.5%. The test method is to stick OCA glue on the back and stick it on the black acrylic plate. After sticking, use a degassing machine to degass, and wipe the surface clean after degassing. In this embodiment, the average reflection of 380-780nm is 0.77 / 0.74%, and the average reflection of 400-700nm is 0.26 / 0.28%, which means that the optical effect is OK.

[0071] Test method: stick OCA glue on the back and stick it on a black acrylic board. Use a degassing machine to degas. Wipe the surface clean after degassing. The L* value here represents brightness. This embodiment reduces the a* value and reduces the red color, making the color look more neutral or cool.

[0072] Example 5

[0073] The AR film of this embodiment includes a PC substrate layer with a thickness of 100 μm and a different application range. The upper and lower primer layers made of polyester emulsion are respectively provided on both sides of the substrate layer through a coating process. The upper and lower primer layers are respectively provided with an upper HC hardening layer and a lower HC hardening layer through a coating process. Both are obtained by coating with an acrylic resin coating liquid. The coating thickness of the upper HC hardening layer is 0.3 μm, and the coating thickness of the lower HC hardening layer is 4.1 μm. After coating, a 150 μm high-temperature protective film is attached to the lower HC hardening layer to ensure the appearance protection of the film surface and the stability of the coating during the magnetron sputtering coating process. A primer layer is then plated on the upper HC hardening layer through a magnetron sputtering process to increase the adhesion of the bottom layer. The raw material of the primer layer can be SiO2, and the coating of the primer layer greatly improves the adhesion performance of the film surface. A first niobium oxide (NB2O5) layer (150nm) for increasing transmittance is plated on the base layer, a first silicon dioxide (SIO2) layer (160nm) for reducing reflection is plated on the first niobium oxide layer, a first mixed target layer (100nm) is formed on the first silicon dioxide layer, the target material ratio (Si:Al is 98:2), a second niobium oxide layer (5-280nm) for increasing transmittance is plated on the first mixed target layer, a second mixed target layer (100nm) for reducing reflection is plated on the second niobium oxide layer, the target material ratio (Si:Al is 85:15), a metal nickel-chromium (NiCr) layer (8nm) for increasing hardness, wear resistance and corrosion resistance is plated on the second mixed target layer, the target material ratio (nickel accounts for 50%, chromium accounts for 50%), and then a second silicon dioxide layer (40nm) is plated on the metal nickel-chromium layer.

[0074] The unified test method is that the film material is placed on the glass panel, and the pencil hardness tester is loaded with 500g to test the hardness of the coating surface. According to the test index requirements, ≥3H (500g), the test instrument model is ASTM D3363, and the pencil hardness test in this embodiment meets the requirements.

[0075] The unified test method is that the film material is placed on the glass panel, the wear-resistant machine is loaded with 1000g, and the wear resistance of the coating surface is tested. The wear resistance of this embodiment can reach 5000 times without scratches on the surface.

[0076] Unified test method, before the ring test, the back side is attached with OCA glue and attached to the transparent glass. After the attachment, the degassing machine is used for degassing. After degassing, the surface is wiped clean, and the test is 100℃ water temperature boiling for 3 / 5h. The 100 grids of this embodiment for 3h are 5B, and the 5h of this embodiment are 5B; the double 85 ring test (high temperature 85℃, high humidity 85%) is tested for 32 days. The 100 grids of this embodiment are 5B, and the 5B of this embodiment are all 5B; the high temperature ring test (95℃) is tested, the 100 grids of this embodiment for 32 days are 5B, and the 5B of this embodiment for 36 days; the low temperature ring test (-40℃) is tested, the 100 grids of this embodiment for 32 days are 5B, and the 5B of this embodiment for 36 days; the sunlight resistance ring test (light 0.55w / (m 2 .nm), wavelength 340nm, filter Extended UV-Q / B, 3.8h of light + 1h of darkness as one cycle. The temperature of the illuminated blackboard was set at 89°C, the temperature of the box was 63°C, and the humidity was 50%; the temperature of the box and blackboard was set at 38°C and the humidity was 95% in the dark stage. In this example, the average of 100 grids was 5B after 32 days, and the average of 100 grids was 5B after 36 days.

[0077] According to the optical test requirements, the total light transmittance of the bare film test can reach more than 95%, and the spectral transmittance of 400-700nm can reach more than 93%. There is basically no significant difference in the transmittance of the samples in this embodiment, indicating that the optical effect is OK.

[0078] According to the optical test requirements, the average reflection of 380-780nm is less than 1.0%, and the average reflection of 400-700nm is less than 0.5%. The test method is to stick OCA glue on the back and stick it on the black acrylic plate. After sticking, use a degassing machine to degass, and wipe the surface clean after degassing. In this embodiment, the average reflection of 380-780nm is 0.77 / 0.74%, and the average reflection of 400-700nm is 0.26 / 0.28%, which means that the optical effect is OK.

[0079] Test method: stick OCA glue on the back and stick it on a black acrylic board. Use a degassing machine to degas. Wipe the surface clean after degassing. The L* value here represents brightness. This embodiment reduces the a* value and reduces the red color, making the color look more neutral or cool.

[0080] Table 6 Color comparison between Examples 2-5 and Comparative Example 1

[0081]

[0082] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0083] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. An AR film comprising the substrate layer, In a direction away from the substrate layer, a lower primer layer and a lower HC hardening layer are sequentially arranged on one side of the substrate layer; In the direction away from the substrate layer, an upper primer layer, an upper HC hardening layer, a primer layer, a first niobium oxide-plated layer, a first silicon dioxide-plated layer, a first mixed target layer, a second niobium oxide-plated layer, a second mixed target layer, a metal nickel-chromium-plated layer and a second silicon dioxide-plated layer are sequentially arranged on the other side of the substrate layer; wherein the metal nickel-chromium-plated layer has a thickness of 0.1-10 nm, and the nickel content of the layer is 40-95 wt%, and the balance is chromium; The base layer, the first niobium oxide coating layer, the first silicon dioxide coating layer, the first mixed target coating layer, the second niobium oxide coating layer, the second mixed target coating layer and the second silicon dioxide coating layer are formed by magnetron sputtering.

2. The AR film according to claim 1, characterized in that The gas bombarding the target material during the magnetron sputtering is argon gas.

3. The AR film according to claim 2, characterized in that: The mass ratio of silicon and aluminum elements in the target material for coating the mixed target layer is: Si:Al=(80-95):(20-5).

4. The AR film according to claim 1, characterized in that The target material of the bottom layer is selected from: SiO2, Ti, Si, Al, MgF2, SiO, Sn, and Y.

5. The AR film according to claim 1, characterized in that: The substrate layer is selected from a PET layer, a PI layer, a SRF layer, a TAC layer, a COP layer, and a PC layer.

6. The AR film according to claim 2, characterized in that: During the magnetron sputtering, the reaction gas of the target material is a mixed gas, and the mixed gas at least includes nitrogen and oxygen.

7. The AR film according to claim 6, characterized in that: The mixed gas includes oxygen for controlling voltage, and the content of the oxygen therein is 5-10 v / v%.

8. The AR film according to any one of claims 1 to 7, characterized in that: The outermost layer away from the substrate layer also includes a high temperature protection film.

9. A light-transmitting component, comprising a light-transmitting carrier and the AR film according to any one of claims 1 to 8 formed on the light-transmitting carrier.

10. An electronic device comprising a main body and the light-transmitting component according to claim 9 connected to the main body.

Citation Information

Patent Citations

  • Low sheet resistance transparent conductive film

    CN111916251A

  • Antistatic AR film and preparation method thereof

    CN112987135A

  • High-weather-resistance high-reflection film and preparation process thereof

    CN118465899A

  • AR film with better physical properties and preparation process thereof

    CN118884582A

  • Dimming film

    CN212181065U